2010
DOI: 10.1371/journal.pone.0013400
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trajectory of White Spot Syndrome Virus (WSSV) Genome Shrinkage during Spread in Asia

Abstract: BackgroundWhite spot syndrome virus (WSSV) is the sole member of the novel Nimaviridae family, and the source of major economic problems in shrimp aquaculture. WSSV appears to have rapidly spread worldwide after the first reported outbreak in the early 1990s. Genomic deletions of various sizes occur at two loci in the WSSV genome, the ORF14/15 and ORF23/24 variable regions, and these have been used as molecular markers to study patterns of viral spread over space and time. We describe the dynamics underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 56 publications
(123 reference statements)
6
54
0
Order By: Relevance
“…The major fall out of the situation is the impediment which it imposes on the isolation of crustacean viruses [15,16,43]. The fact is that the requirement of continuous cell lines is so high to investigate the radiating viral threats to shrimp aquaculture [21,88,93].…”
Section: Introductionmentioning
confidence: 99%
“…The major fall out of the situation is the impediment which it imposes on the isolation of crustacean viruses [15,16,43]. The fact is that the requirement of continuous cell lines is so high to investigate the radiating viral threats to shrimp aquaculture [21,88,93].…”
Section: Introductionmentioning
confidence: 99%
“…By quantifying evolutionary divergence using a simple mathematical model, Zwart et al (2010) deduced that ORF23/24, but not ORF14/15, sequence variation correlates well with when a WSSV isolate was obtained compared to when WSD first emerged in shrimp in Taiwan, and not with geographical distance from Taiwan. The analysis suggested that the WSSV type that emerged in crayfish being farmed in China in 2006 was a descendent or relative of the virus type that emerged in penaeid shrimp farmed in East Asia in the early to mid-1990s.…”
Section: T G T T T Wssv-tw 6 T T T G T T Wssv-th 6 T G G mentioning
confidence: 99%
“…Sequence analyses of these 2 indel regions in other Asian WSSV strains have identified intermediatelength deletions (Dieu et al 2004, Zwart et al 2010. For example, WSSV strains from China contain shorter Indel-II deletions (1168 to 5928 bp) compared with WSSV-TW, while strains from Vietnam contain a medium-length Indel-II deletion (~8539 bp) not yet found in strains examined from other geographic regions (Dieu et al 2004; see also Yang et al 2001, Lan et al 2002, Tan & Shi 2011.Indel-I and Indel-II regions are now being used as molecular markers to study WSSV epidemiology (Dieu et al 2004, Zwart et al 2010, and Indel-II is proving to be particularly useful for examining the spatiotemporal spread of WSSV at regional (Dieu et al 2010) and intercontinental levels (Zwart et al 2010). Data on Indel-II support a hypothesis that all WSSV strains affecting farmed shrimp have a recent common ancestor.…”
mentioning
confidence: 99%
“…2011). WSSV genome lengths estimated from analyses of Indel-I and Indel-II lengths suggest that genome shrinkage rates since 1992 are decreasing over time (Zwart et al 2010). While increased Indel-I and Indel-II deletion lengths have been associated with increased WSSV virulence (Marks et al 2005, Zwart et al 2010, an early study reported reduced virulence with increased Indel-II deletion lengths (Lan et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation